PELATIHAN PEMBUATAN PUDING STRAWBERRY SEBAGAI CEMILAN KAYA NUTRISI GUNA MENCEGAH STUNTING - Pagdya Haninda Nusantri Rusdi; Kartika Mariyona; Mega Ade Nugrahmi (Universitas Muhammadiyah Luwuk, 2023)
One form of failure to thrive and the consequences of poor nutrition from pregnancy to birth which is a very high problem in Indonesia is Stunting. One way to prevent stunting from increasing is by making nutrient-rich snacks in the form of strawberry fruit pudding which will later be prepared with various kinds of food ingredients needed for children under five. This service activity takes the form of training for cadres in making strawberry pudding as a nutrient-rich snack to prevent stunting in Nagari Balingka, Agam Regency. The method for implementing this PPM is by means of lectures and direct demonstrations together with posyandu cadres. As a result of this activity, the cadres were able to make strawberry pudding and provide education to mothers of toddlers in Nagari Balingka, Agam Regency